2013
DOI: 10.1186/1756-0500-6-184
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic acid and the reduction of blood loss in total knee and hip arthroplasty: a meta-analysis

Abstract: BackgroundTranexamic acid (TXA) is an antifibrinolytic drug used as a blood-sparing technique in many surgical specialties. The principal objective of our meta-analysis was to review randomized, controlled trials (RCT) comparing total blood loss and the number of patients receiving allogeneic blood transfusions with and without the use of TXA for knee (TKA) and hip (THA) arthroplasty.MethodsStudies were included if patients underwent primary unilateral TKA or THA; the study involved the comparison of a TXA tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
112
0
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(125 citation statements)
references
References 52 publications
3
112
0
10
Order By: Relevance
“…Among those strategies, TXA administration has proved to effectively decrease transfusion rates, particularly in meta-analyses of trials [7][8][9] and with repeated dose [10]. Interest remains in clarifying how blood transfusion can even be effectively avoided after TKA.…”
Section: Introductionmentioning
confidence: 99%
“…Among those strategies, TXA administration has proved to effectively decrease transfusion rates, particularly in meta-analyses of trials [7][8][9] and with repeated dose [10]. Interest remains in clarifying how blood transfusion can even be effectively avoided after TKA.…”
Section: Introductionmentioning
confidence: 99%
“…14 TXA use decreases blood loss and necessitates fewer blood transfusions. 15 TXA reduces blood loss by 29% and reduces the risk of receiving a blood transfusion by 45%. 16 Intra-articular TXA reduces blood loss and knee joint swelling.…”
Section: Discussionmentioning
confidence: 99%
“…Méthode Nous avons mis en oeuvre une politique de qualité des soins afin de procéder à l'administration universelle de TXA par voie intraveineuse à une dose de 20 mgÁkg -1 à tous les patients admissibles subissant une arthroplastie totale de la hanche ou du genou entre le 21 Administration of tranexamic acid (TXA) has been shown to reduce blood loss and allogeneic red blood cell (RBC) transfusion in cardiac and various noncardiac surgical procedures. 1 Many randomized controlled trials, [2][3][4][5][6] systematic reviews, and meta-analyses [7][8][9][10][11] have shown that systemic and topically administered TXA reduces allogeneic RBC transfusion in hip or knee arthroplasty surgery. Recent observational studies have also shown an association between TXA use and reduced RBC transfusion.…”
Section: Résuméunclassified